Family Group Conferencing with BME Families in Scotland. Issue 2 (15th March 2017) - Valenti, Katerina
Abstract : This article explores the use of family group conferencing (FGC) in social work with children and families from black and minority ethnic (BME) backgrounds living in Scotland. It does so by presenting the views of social work practitioners on issues that are highlighted as significant in the existing literature about the use of FGC with BME families. Eight semi-structured interviews with key informants were carried out as part of the work for a Master of Social Work dissertation, and this is followed by a reflexive discussion from the perspective of the author as a newly qualified social worker working in a statutory children and families' team. The article ends with suggestions for maximising the opportunities for BME families to participate in, and benefit from, FGC.